The Multifaceted Image of Women in Wendy Wasserstain’s The Heidi Chronicle: A Feminist Analysis - Asna, Ulfatul (English Literature Study Program, 2024)
The study aims to explores Heidi’s woman image in Wendy Wasserstain's The Heidi Chronicle, focusing on the physical, physic, and social aspects of women. The research design is literary criticism, using play The Heidi Chronicle as the data source. The method used is descriptive qualitative research, using a feminist approach and Tong's liberal feminism theory as a theoretical framework. Based on the background of the study above, problems of the study discussed in this research are: (1) How is the physical image of Heidi’s character portrayed in Wasserstain’s The Heidi Chronicle? (2) How is the physic image of Heidi’s character portrayed in Wasserstain’s The Heidi Chronicle? (3) How is the social image of Heidi’s character portrayed in Wasserstain’s The Heidi Chronicle? The physical image of women in the play is seen through the physical characteristics of Heidi Holland, who experiences adulthood, menstruation, and motherhood. She is simple but well-dressed. The physic image of women is seen through Heidi's inner conflict over marriage and career choices, and her responsibility for her destiny. The social image of women in the play is depicted as a mother, breadwinner, and a woman who influences society. In society, Heidi is portrayed as a woman with a good career, who participates in social activities in art and women's equality. Overall, the study highlights the complex and multifaceted image of women in the play.